P2X7 Receptor in the Management of Energy Homeostasis: Implications for Obesity, Dyslipidemia, and Insulin Resistance - Coccurello, Roberto; Volonté, Cinzia (Frontiers in Endocrinology, 2020)
Whole-body energy metabolism entails the highly-regulated balance between food intake, nutrient breakdown, energy generation (ATP) and energy storage for the preservation of vital functions and body mass. Purinergic signaling has attracted increasing attention in the regulatory mechanisms not only for the reverse processes of white adipose tissue lipogenesis and lipolysis, but also for brown adipocyte-dependent thermogenesis and leptin production. This regulatory role has remarkable implications in the handling of body’s energy expenditure and energy reservoir. Hence, selected purinergic receptors can play a relevant function in lipid metabolism, endocrine activity, glucose uptake, ATP-dependent increased expression of uncoupling protein 1 and browning of adipose tissue. Indeed, purinergic P2 receptors regulate adipogenesis, lipid metabolism and are involved in adipogenic differentiation. In particular, the ionotropic ATP-activated P2X7 subtype is involved in fat distribution, as well as in the modulation of inflammatory pathways in white adipose tissue. Within this context, very recent evidence has established a direct function of P2X7 in energy metabolism. Specifically, either genetic deletion (P2X7 knock out mice) or subchronic pharmacological inhibition of the receptor, produces a decrease of whole-body energy expenditure and, concurrently, an increase of carbohydrate oxidation. As further evidence, lipid accumulation, increased fat mass distribution and weight gain is reported in P2X7-depleted mice. Conversely, the stimulation of P2X7 enhances energy expenditure. Altogether, this knowledge supports the role of P2X7 signaling in the fight against obesity and insulin resistance, as well as in the promotion of adaptive thermogenesis.